2001
DOI: 10.1046/j.1469-0705.2001.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical length at 22–24 weeks of gestation: comparison of transvaginal and transperineal‐translabial ultrasonography

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 12 publications
8
59
0
9
Order By: Relevance
“…Cicero et al found that at 22-24 weeks of gestation, the cervix could be visualized adequately by TPUS in about 80% of patients, and measurements of the cervical length obtained by TPUS were very similar to those obtained by TVUS. 13 Specifically, during transperineal imaging of certain patients, some shadowing prevented visualization of part of the cervix, resulting in an artificially shortened appearance of the cervix (Figure 4). We tried to avoid these problems by elevating the patients' hips using a thick cushion.…”
Section: Discussionmentioning
confidence: 99%
“…Cicero et al found that at 22-24 weeks of gestation, the cervix could be visualized adequately by TPUS in about 80% of patients, and measurements of the cervical length obtained by TPUS were very similar to those obtained by TVUS. 13 Specifically, during transperineal imaging of certain patients, some shadowing prevented visualization of part of the cervix, resulting in an artificially shortened appearance of the cervix (Figure 4). We tried to avoid these problems by elevating the patients' hips using a thick cushion.…”
Section: Discussionmentioning
confidence: 99%
“…Transabdominal ultrasound requires a full bladder, which may influence the results falsely 18 . Transperineal-derived images have been shown to be inadequate in more than 50% of cases, while patient acceptability was similar compared with TVS 19 , which was introduced 15 years ago in singleton and later in multiple pregnancies 9,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…По результатам иссле-дования вычисляется срок родов и задержка внутриутробного развития плода, принима-ются решения о тактике ведения беремен-ности [5,6]. С помощью ТПУС производится оценка длины, структуры шейки матки, а так-же оценка риска развития истмико-церви-кальной недостаточности [7][8][9]. Ряд авторов указали на результаты мониторинга родовой деятельности, получение информации о сте-пени открытия шейки матки, продвижении, фиксации головки и ее размерах, как весьма важные для прогноза родов [10][11][12][13][14][15].…”
Section: анализ литературных данных и постановка задачи исследованияunclassified